Controle ativo de ruído em dutos utilizando processadores digitais de sinais - Delfino, Leandro César (2005)
Acoustical noises are known as pollution sources that cause adverse effects in human life. Considerable investigations have been done to development of the new technologies in Active Noise Control. This work presents and experimentally analyses algorithms of Active Noise Control in Ducts presented in literature, including Feedforward algorithms, Feedback algorithms and Hybrid algorithms that uses both concepts. The identification of secondary path and feedback path is presented and solutions are discussed. In this way, methods of off-line and on-line modeling are presented. A short introduction about acoustics in ducts is presented and some effects that the acoustical noise can cause in human being are also discussed. Problems about the sensors and actuators displacement in the duct system, causality and signal conditioning are also argued here. An introduction about Digital Signal Processors (DSPs) e some particularities found in the development of this works are presented. In order to evaluate the control algorithms performance, an experimental acoustic duct using a standard PVC water pipe was built, where those algorithms were implemented in a DSP platform TMS320LF240A from Texas Instruments®. An analysis is done about the difficulty and recourses used for which algorithm implemented. This work ends presenting and discussing the obtained results for the different control procedures studied and pointing to some future works.